2005
DOI: 10.1177/112067210501500503
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Congenital Entropion of the Lower Eyelid: Incisional versus Rotational Surgery

Abstract: The authors consider both techniques satisfactory, but the procedure of choice, considering the age of the patients and previous studies, remains rotational sutures because of its simplicity, quickness, and low risk of complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A. Deka and S.P. Saikia orbit Incisional and rotational surgeries are very effective for congenital entropion (Serafino et al, 2005). However, a previous study had showed the effectiveness of botulinum toxin injection in children with congenital entropion (Christiansen et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…A. Deka and S.P. Saikia orbit Incisional and rotational surgeries are very effective for congenital entropion (Serafino et al, 2005). However, a previous study had showed the effectiveness of botulinum toxin injection in children with congenital entropion (Christiansen et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…While variations of the Hotz procedure have previously been described in congenital entropion and epiblepharon repair, these approaches use the procedure for the purposes of everting the anterior lamella. 12,16,19 Unlike these previous studies, the reformation of the lower eyelid crease described herein is simply done to minimize the appearance of the incision or scar; it is not intended to alter the position of the anterior lamella or overlying lashes. Instead, eversion is accomplished through the rotational sutures.…”
Section: Discussionmentioning
confidence: 99%
“…Transection of the anterior layer of the LER was hypothesized as the cause, and repair was accomplished by reforming the crease using the Hotz procedure 2 . The everting force provided by the Hotz procedure may also contribute to rotation of the lid as the procedure performed in isolation was reported to result in satisfactory correction of congenital entropion in which posterior eyelid retractor disinsertion was the primary cause 12 . However, in the current proposed technique, the modified Hotz procedure is intended for cosmetic benefit, not lid eversion.…”
Section: Discussionmentioning
confidence: 99%
“…reported a series of successful lower lid congenital entropion repair utilizing a rotational suture technique similar to ours, as well as incisional technique. 5 Bosniak reported a case of congenital upper lid entropion associated with a tarsal kink. His technique involved a rotational suture that entered the upper eyelid conjunctiva near the base of the lid, then carried the sutures through the tarsus and emerged through the skin superiorly (the opposite direction of our sutures).…”
Section: Discussionmentioning
confidence: 99%